The Prescription of Long-Acting Opioids for Working-Age Patients With Workers' Compensation or Chronic Illness Diagnoses in the United States: From the National Ambulatory Medical Care Survey (NAMCS), 2010 to 2016. Issue 3 (March 2021) - Topper, Leah; Rosas, Valeria Menendez; Aarkoti, Malathi; Doucette, John; Nabeel, Ismail
Abstract : Objective: To examine associations of workers' compensation, chronic conditions, age, sex, and race/ethnicity with primary prescription of long-acting opioids (LAO) among working-age patients in ambulatory care. Methods: Using the National Ambulatory Medical Care Survey (2010 to 2016), we conducted descriptive, bivariate, and multivariate logistic regression analyses of patients aged 18 to 64 with an LAO as their primary medication. Results: Those prescribed an LAO were more likely to be men (adjusted odds ratio [aOR] = 1.48, 95% CI 1.13, 1.91), have workers' compensation (aOR = 2.00, 95% CI 1.12, 3.57), or have diagnoses of lower back pain (aOR = 4.70, 95% CI 3.51, 6.29), arthritis (aOR = 1.53, 95% CI 1.11, 2.09), or depression (aOR = 1.69; 95% CI 1.24, 2.31). Hispanic ethnicity/race had a lower likelihood of LAO use compared with non-Hispanic White (aOR = 0.58; 95% CI 0.37, 0.90). Conclusions: Male sex, workers' compensation, and diagnoses of lower back pain, arthritis, or depression were independently associated with increased LAO prescription odds. Abstract : Supplemental Digital Content is available in the text